Healthcare adjustments and concerns: a qualitative study exploring the perspectives of healthcare providers and administrative staff during the COVID-19 pandemic in Saudi Arabia - Alkathlan, Mohammed S.; Alsuyufi, Yasir A.; Alresheedi, Abdulhamid F.; Khalil, Rehana; Sheiq, Parveen Anjum; Alotaieq, Suliman S.; Almithn, Abdullah A.; Alissa, Ibrahim I.; Alayyaf, Hamad F.; Alharbi, Raed M.; Alkhamis, Ibrahim A.; Al-Wutayd, Osama (Frontiers in Public Health, 2023)
Background: Healthcare systems have modified their strategies to manage their staff, supplies, and space to deal systematically with the COVID-19 pandemic. This research aimed to explore the nature of hospital adjustments and the concerns of healthcare providers and administrative staff working in Governmental and private hospitals throughout the Qassim Region of the Kingdom of Saudi Arabia (KSA) during the pandemic. Methods: Semi-structured in-depth interviews were conducted with 75 purposively selected healthcare providers and administrative staff working at three main hospitals in the Qassim Region, KSA. The maximum variation sampling technique was utilized. All interviews were audiotaped, transcribed verbatim, and analyzed thematically. Results: Four core themes were identified in this paper: (1) changes in hospital policy and procedures, (2) workforce management, (3) the well-being of the workforce, and (4) apprehensions and expectations of the workforce. The participants showed satisfaction with timely administrative decisions and new policies during the COVID-19 pandemic. Furthermore, the psychological health of healthcare professionals was affected more than their physical state. Finally, the providers perceived the emergence of multiple concerns in the coming months. Conclusion: Although healthcare providers were initially overwhelmed, they gradually accepted new administrative policies. Numerous innovative interventions effectively reduced their physical workload and increased their productivity, but they remained significantly affected by a wide range of psychological disorders, with a high prevalence of obsessive-compulsive disorder. There were some apprehensions about the new SARS-CoV-2 variant, but the majority were optimistic.